1998
DOI: 10.1007/s002560050359
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord compression caused by thoracic vertebral hemangioma involving only the posterior elements of two contiguous vertebrae

Abstract: An unusual case of symptomatic thoracic vertebral hemangioma involving two contiguous vertebrae but confined to the posterior elements is presented. The lesion displaced and compressed the cord. The diagnosis was not considered prior to biopsy. There was uncontrolled bleeding at biopsy. Only partial surgical resection was performed, with incomplete relief of motor weakness after initial surgery. The patient refused further surgical resection. Motor power was gradually recovered after a course of postoperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Vertebral height was normal in 15 cases (72 %; cases 1, 3) [5,6,20,43,45,49,51,53,54,55,57]. In 2 cases (4 %) there was loss of anterior vertebral height of approximately 33 % (case 2) [6].…”
Section: 52]mentioning
confidence: 87%
See 3 more Smart Citations
“…Vertebral height was normal in 15 cases (72 %; cases 1, 3) [5,6,20,43,45,49,51,53,54,55,57]. In 2 cases (4 %) there was loss of anterior vertebral height of approximately 33 % (case 2) [6].…”
Section: 52]mentioning
confidence: 87%
“…In all of these cases, lesions were hypointense relative to spinal cord on T1WI (cases 1-3) [3,6,20,51,53,57]. Five of these lesions contained signal voids (20 %; case 1) [6,53,57].…”
Section: 52]mentioning
confidence: 91%
See 2 more Smart Citations
“…52 In the 1970s it was suggested that angiography could be used not only to confirm the diagnosis but also to perform endovascular embolization of the feeding arteries in order to reduce vascularity of the tumor and decrease blood loss during surgery. 8,19,22,37,50,53,59,73 The benefits of embolization were confirmed in a systematic review that included 51 patients with aggressive vertebral hemangiomas. This study found that in the group that received preoperative embolization, blood loss was significantly less than in the group that did not (980 vs 1629 ml, respectively).…”
Section: Endovascular Embolizationmentioning
confidence: 93%